A Correlation level of knowledge about cervical cancer with cervical cancer prevention behavior in adolescent women class X & XI AT SMK Muhammadiyah Berbah - Hanifah, Nur; Handayani, Sri (Jurnal Kesehatan Samodra Ilmu (JKSI), 2022)
Background : Cervical cancer is the second most common malignant tumor in women in women world and the most common types of cancer found in women in developing countries, including Indonesia. It is estimated that the number of people with this cancer will increase in the future due to lifestyle changes. The incidence of cervical cancer in Southeast Asia is 30-44.9 per 100,000 women each year. The estimated incidence of cervical cancer is 385,540 cases worldwide and in the last 3 years it has increased to 26.1 per 100,000 population. Purpose: to determine the level of knowledge with cervical cancer prevention behavior in adolescent girls in class X-XI SMK Muhammadiyah Brebah. Research method: this is a quantitative research with a non- experimental. The research was carried out at SMK Muhammadiyah Brebah. The sampling technique used is total sampling. With respondents as many as 93 young women class X and XI SMK Muhammadiyah Brebah. The instrument used is a questionnaire. Results: From the results of the level of knowledge with preventive behavior of adolescent girls in grades X and XI about cervical cancer, the correlation coefficient was 0.241 with a significance of 0.017. Conclusion: There is a relationship between the level of knowledge about cervical cancer and the behavior of preventing cervical cancer for female adolescents in class X and XI at SMK Muhammadiyah Berbah.